(untitled) - Hoey, Michael (Oxford, 1996)
Passages of authentic text are analysed to demonstrate the operations of patterns of lexis across sentence boundaries and over considerable distances within and between texts. These insights are related to a comprehensive theory of language, in which 'lexis' and 'text' are shown to be important levels of language organization. Implications for the teaching of reading and writing are also discussed. First Prize English Speaking Union's Duke of Edinburgh Book Competition
Keywords: English language,Lexicology; Study and teaching